Pengembangan Aplikasi Stok Barang Pada Cv. Lentera Abadi Nusantara Menggunakan Metode Waterfall - firman, Firmansyah Budi Utomo; nungky, Nungky Awang Chandra (CV. Utility Project Solution, 2023)
Lentera Abadi Nusantara is currently still using a manual system in the process of recording incoming and outgoing goods, in the business process the warehouse department records every time goods come in which is equipped with a travel document and proof of transaction and also when goods leave the warehouse, the stock is recorded automatically. manual in the book, which is then recapitulated and inputted into Microsoft Excel to report stock data every month, while the obstacle that occurs is the difficulty in finding stock of goods and processing data. In this way, the system that runs often encounters problems such as incompatibility of incoming goods data and recording of goods recurring. Therefore, we need an inventory information system that makes it easier for employees. It is hoped that the existence of this item list information system will help employees to manage incoming and outgoing goods. Inventory management is designed using a system development method, namely Agile Software Development which can later facilitate the management of incoming and outgoing goods at CV Lentera Abadi Nusantaraa and can suit the needs of users of the system. Keywords: Stock Goods, Waterfall, Web